2022
DOI: 10.1155/2022/1531738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Enteral Nutrition Support Combined with Chemotherapy on Related Complications and Immune Function of Patients after Radical Gastrectomy

Abstract: Objective. The purpose was to analyze the effect of early enteral nutrition (EEN) support combined with chemotherapy on related complications and immune function in patients after radical gastrectomy. Methods. 80 patients with gastric cancer treated in our hospital from March 2019 to March 2020 were selected as the research objects and divided into the experimental group and control group according to the random number table, with 40 cases in each group. The control group received chemotherapy only after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Consequently, when refeeding, these patients are more prone to electrolyte disturbances and sodium and water retention as the electrolytes are further displaced ( 27 ). In addition, the lack of food and gastrin stimulation of the intestinal mucosa causes a decrease in the secretion of gastric acid, bile, and other digestive juices, resulting in weakened bactericidal capacities of the intestines, as well as a proliferation and displacement of intestinal toxins, causing an intestinal or systemic inflammatory response that affects the digestive and absorption functions of the intestine ( 31 ). These factors are ultimately detrimental to the implementation of EN.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, when refeeding, these patients are more prone to electrolyte disturbances and sodium and water retention as the electrolytes are further displaced ( 27 ). In addition, the lack of food and gastrin stimulation of the intestinal mucosa causes a decrease in the secretion of gastric acid, bile, and other digestive juices, resulting in weakened bactericidal capacities of the intestines, as well as a proliferation and displacement of intestinal toxins, causing an intestinal or systemic inflammatory response that affects the digestive and absorption functions of the intestine ( 31 ). These factors are ultimately detrimental to the implementation of EN.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in a study by Wang et al [ 26 ], early enteral nutritional support was found to improve immune function in patients after radical chemotherapy gastric cancer to reduce the occurrence of postoperative complications. This is largely consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies examined oral or enteral nutrition support before or after cancer surgery; the studies varied in the route and contents of nutrition support delivered and the timing of the intervention and comparison groups. Thirteen studies examined oral or enteral nutrition support before or after chemotherapy and/or radiation; however, they also considerably varied in the route and contents of nutrition support delivered, populations, and timing of the intervention and comparison groups ( 72 , 89 , 174 , 179 , 181 , 184 , 186 , 195 , 205 , 208 , 210 , 213 , 218 ). Finally, 4 studies examined TPN across cancer and treatment types ( 173 , 185 , 209 , 211 ).…”
Section: Effect Of Nutrition Interventions On Symptomsmentioning
confidence: 99%